Scattering of Electromagnetic Pulses on Different Dielectric Resonator Systems - A. A. Trubin (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ, 2018)
The theory of scattering of electromagnetic pulses in a transmission line on systems of coupled dielectric resonators of different shapes and dielectric permittivity is developed. General analytic expressions for envelope pulses scattered on band-pass and rejection dielectric filters are obtained. It is shown that for identical resonators the expressions found in special cases become known. The results of calculating the rectangular and Gaussian pulses scattered by bandpass and bandstop filters of the terahertz and infrared wavelengths, constructed on various dielectric resonators in various transmission lines, are presented.